Kafka’s unspoken philosophy of law - Prole, Dragan (Array, 2021)
In the first part of the paper, the author pays close attention to the fact that in Kafka’s diaries and correspondence, we find a notable absence of his professional life. If we never knew the famous writer was a law expert, we would hardly be able to determine that from his personal writings. There is no mention of his studies of law, professional aspirations, problems or procedural interests related to judicial practice, or difficulties or achievements in the workplace. Surprisingly, within the complex hierarchy of business interactions, the writer occupied a very high position. The performed analysis uncovers an essential, but a barely recognisable feature of Kafka’s works. Above all, they try to alert us that the feudal world is still alive and well, that in the modern times we only see the multiplication of the former sovereigns whose role was to impose the laws onto others but can personally be excused. The works of Rudolf von Jhering, one of the best-known philosophers of the law of the time, and Hans Gross, the famous founder of criminology and Kafka’s professor at Charles University, Prague, were thematised in order to determine the dimensions of the writer’s crucial preoccupation – to deconstruct the social Darwinist theories of the criminal law.